EFFECT OF ETHICS, INDEPENDENCY, AND AUDIT FEE ON AUDIT QUALITY AS THE IMPACT OF COVID-19 - Nurcahya, Yulida Army; P, Diah Agustina (2021)
The pandemic that occurred and hit the whole world quickly caused various crises in the health, economic and social fields that affected all activities of the world community. This is a quantitative study utilizing a descriptive analysis approach. This study uses both primary and secondary data. Purposive sampling was employed to obtain data for this study, utilizing the following respondents' criteria: 1) Respondents were external auditors employed by a Public Accounting Firm (KAP) in the City of Magelang; and 2) Respondents had worked as auditors for a period of at least one year. The Research Instruments Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Hypothesis Testing (Coefficient of Determination Test (R2), F Statistics Test, and Partial Test (t-test)) were used to analyze the data in this study. From the results of the discussion and analysis, it can be concluded that: 1) Ethics variables have no effect on audit quality; 2) Independent variables affect audit quality during the Covid-19 pandemic with a t-count value of 2.088; 3) The Audit Fee variable has an effect on audit quality with a t-count value of 2.213.